Pengaruh Kualitas Auditor, Kondisi Keuangan, Kepemilikan Perusahaan, Disclosure, Pertumbuhan Perusahaanm dan Debt Default terhadap Penerimaan Opini Audit Going Concern: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014 - Hinarno, Elia; Osesoga, Maria Stefani (Ultimaccounting Jurnal Ilmu Akuntansi, 2016)
The objective of this study was to obtain empirical evidence about the effect of auditor's quality, financial condition, company's ownership, disclosure, company's growth, and debt default on the acceptance of going concern audit opinion. The object of this study is the manufacture companies listed in Indonesia Stock Exchange in 2011 -2014. Samples of this research were taken by using purposive sampling as many as 8 manufactures company. Criteria taken among companies that publish annual report with financial statements audited by an external auditor in the year 2011 – 2014, financial statements period is begin on 1 January and ended on 31 December, using rupiah as a currency, and have a net loss at least 2 periods in a row. This research use regression logistic, because the dependent variable measured by nominal scale. In testing the simultaneous significant auditor's quality, financial condition, institutional's ownership, managerial's ownership, disclosure, company's growth, and debt default have significant effect towards going concern audit opinion. In T test, in partial, the independent variabel auditor's quality, financial condition, institutional's ownership, managerial's ownership, disclosure, company's growth, and debt default, does not have a significant effect on the auditor in the provision of going concern audit opinion. Keywords: Auditor's Quality, Company's Growth, Debt Default, Disclosure, Financial Condition, Going Concern, Institutional's Ownership, Managerial's Ownership.